Pregnancy-related claustrophobia. Issue 1 (13th January 2022) - Keane, Nessa; Farrell, Amy; Hallahan, Brian
Abstract : A 35-year-old primigravida presented with significant anxiety symptoms at 26 weeks' gestation. Symptoms were preceded by a nightmare about her upcoming labour. She developed repetitive intrusive thoughts of being trapped emotionally and physically in her pregnancy. Her symptoms were suggestive of new-onset claustrophobia associated with pregnancy, which has not been previously reported on. Her symptoms ameliorated with a combination of cognitive–behavioural therapy and pharmacotherapy (sertraline and low dose quetiapine). The later stages of pregnancy were associated with minimal symptoms and the resolution of her subjective 'entrapment'. A subsequent pregnancy resulted in similar although less severe symptomatology. No postpartum anxiety symptoms were demonstrated on both occasions. Anxiety symptoms can adversely impact both the mother and fetus, and thus correct identification and management of pregnancy-related claustrophobia improved symptomatology and functioning and allowed for earlier detection and reduced symptomatology in a subsequent pregnancy.